1996
DOI: 10.1111/den.1996.8.3.180
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Endoscopic Color Doppler Ultrasonography in the Detection of Perforating Veins of Esophageal Varices

Abstract: We studied 118 patients using endoscopic color Doppler ultrasonography (ECDUS) to evaluate perforating veins of esophageal varices. The ECDUS was performed with a PENTAX FG‐32UA or FG‐36UX (7.5 MHz, convex type) and a HITACHI EUB 565 was used as a display device. We defined the perforating veins as communicating vessels between esophageal varices and paraesophageal veins. We evaluated the detection rate and the direction of blood flow in the perforating veins. Color flow images of perforating veins were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…There is little information in the literature on perforating veins. 5,[11][12][13][14] Color Doppler is based on the mean Doppler frequency shift and therefore is a measure of the directional component of the blood velocity moving through the sample volume. Power Doppler, on the other hand, is based on the integrated Doppler power spectrum, and the power in the Doppler signal is related to the number of red blood cells producing the Doppler shift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little information in the literature on perforating veins. 5,[11][12][13][14] Color Doppler is based on the mean Doppler frequency shift and therefore is a measure of the directional component of the blood velocity moving through the sample volume. Power Doppler, on the other hand, is based on the integrated Doppler power spectrum, and the power in the Doppler signal is related to the number of red blood cells producing the Doppler shift.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the usefulness of ECDUS in patients with esophago-gastric varices. 4,5 We have been able to obtain color flow images that graphically show esophageal varices, paraesophageal veins, and perforating veins in patients with esophageal varices.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported on the usefulness of ECDUS (convex-type scanning instruments with forward-oblique viewing) for evaluating the hemodynamics of esophagogastric varices. [1][2][3] We also previously found that the use of Levovist contrast can improve the diagnostic quality of convex-type ECDUS of esophageal variceal patients, yielding a much clearer picture of the hemodynamics. 4 In the present study, we report the usefulness of a new electronic radial ECDUS technique in evaluating the hemodynamics of esophageal varices by comparison with convex-type ECDUS.…”
Section: Introductionmentioning
confidence: 90%
“…5,6 On the other hand, we have reported the usefulness of endoscopic color Doppler ultrasonography (ECDUS) in patients with esophagogastric varices. [7][8][9] With ECDUS, color flow images in blood vessels can be obtained, and ECDUS allows for more detailed observation of the hemodynamics of esophagogastric varices than EUS. In this study, we examined the usefulness of ECDUS for evaluating hemodynamics in cases of rectal varices, and we compared blood flow velocities between rectal varices and esophageal varices.…”
Section: Introductionmentioning
confidence: 99%